Training On Organic Household Waste Processing And Aquaponic Production In Grand Watu Dodol Banyuwangi - Arista, Yuvita Lira Vesti; Khairunnisa, Anita; Iid Mufaidah; Harsanti, Restiani Sih; Chastelyna, Agnes Juniarti; Mahesvara, Titah; Santos , Jonio dos (Bakti Cendana, 2026)
Grand Watu Dodol (GWD) is one of the major tourist destinations in Banyuwangi Regency and attracts a large number of visitors. Tourism activities in the GWD area are accompanied by various trading activities, which inevitably generate organic waste. This waste mainly consists of food residues from visitors, including fruit and vegetable scraps, leftover rice, and uneaten side dishes. At present, this waste is disposed of only at temporary waste disposal sites (TPS), resulting in environmental problems such as unpleasant odors and limited waste-handling capacity.Organic waste generated in the GWD area has considerable potential to be utilized as raw material for compost production and as a growing medium in aquaponic systems or BUDIKDAMBER (Fish Cultivation in Buckets). Leftover rice, fruits, and vegetables can be processed into compost with the assistance of maggot larvae, while root and stem residues can be used as planting media in aquaponic or BUDIKDAMBER systems. Composting not only produces organic fertilizer but also generates maggot larvae that can be utilized as poultry feed. In addition, aquaponic systems can produce vegetables and fish as by-products, which may contribute to nutritional fulfillment and provide additional income for local business actors operating in the Grand Watu Dodol tourist area.